Sosialisasi Literasi Digital untuk Meningkatkan Pemahaman dan Tanggung Jawab Pelajar di SMP dan SMA Manbaul Huda Desa Comok Sinar Jaya - Mesen Khusnul Aisah; Mertha Putri Pratiwi; Mentari Mentari; Melin Maulinta; Mey Mayangsari; Mesiana Mesiana; M Yusuf Amar; Marcelino Akbar Stevano; Merdiyanto Merdiyanto; Anton Widodo (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2025)
Digital literacy socialization is the focus of this study, with the aim of developing and improving the understanding and sense of responsibility of junior high and high school students at Manbaul Huda in Comok Sinar Jaya Village. This is motivated by the rapid development of technology in Indonesia, which has influenced students' learning patterns and behavior. Digital literacy has become an important requirement for students to have relevant, in-depth skills and be able to use them wisely. Digital literacy encompasses not only the ability to operate technological devices, but also an understanding of media ethics, cyber security, and critical thinking skills in dealing with the rapid flow of information. This outreach program was designed with a participatory approach, where students not only received material but also actively discussed and participated in practical simulations. The material was delivered using simple and easy-to-understand language, accompanied by real-life examples from everyday life so that students could more easily relate it to their experiences. The results of the program show a significant positive impact. Students have become smarter in filtering information spread on the internet, more aware of the potential for personal data leaks, and demonstrate a more ethical attitude when interacting on social media. These behavioral changes indirectly encourage the formation of a healthy and positive digital culture in the school environment. Thus, this program is able to support the creation of a young generation that is not only tech-savvy but also responsible in its use.